Magnetic microkayaks: propulsion of microrods precessing near a surface by kilohertz frequency, rotating magnetic fields. Issue 10 (23rd February 2017) - Mair, L. O.; Evans, B. A.; Nacev, A.; Stepanov, P. Y.; Hilaman, R.; Chowdhury, S.; Jafari, S.; Wang, W.; Shapiro, B.; Weinberg, I. N.
Abstract : Rotating microrods magnetized nearly orthogonally to their long axes are actuated near a solid surface, demonstrating precession akin to a kayaker's paddle. Abstract : Surface-swimming nano- and micromotors hold significant potential for on-chip mixing, flow generation, sample manipulation, and microrobotics. Here we describe rotating microrods magnetized nearly orthogonally to their long axes. When actuated near a solid surface, these microrods demonstrate precessing motion, with rods describing a double cone similar to the motion of a kayaker's paddle. The precessing motion induces translation. At 1 kHz, these "microkayaks" move at translational velocities of ≈14 μm s −1 and generate advective flows up to 10 μm s −1 .